Pengaruh Harga Tiket Dan Kualitas Pelayanan Cabin Terhadap Keputusan Pembelian Pengguna Jasa Maskapai Garuda Indonesia Di Bandar Udara Adi Soemarmo - Nurlela, Siti; Fryda Fatmayati (MAMEN: Jurnal Manajemen, 2022)
This study aims to determine whether there is an effect of ticket prices and cabin service quality on the purchasing decisions of Garuda Indonesia Airline Service Users at Adi Soemarmo International Airport. This research technique uses quantitative methods. Data was collected using a questionnaire with a sample size of 100 respondents. The data analysis technique used descriptive analysis, the instrument test was validity and reliability test, hypothesis test used simple linear regression analysis, t test, f test, and the coefficient of determination which was processed using SPSS.20. In this study the results obtained that ticket prices and service quality have a positive and significant effect simultaneously on purchasing decisions with an F-count value of 34.779 > T-table 1.996 with a significance of 0.000 > 0.05. The coefficient of determination is 41.8% that purchasing decisions are influenced by ticket prices and service quality, while the remaining 58.2% is influenced by other variables. results Based on the research above, the ticket price offered must be in accordance with the quality of service in order to influence customer purchasing decisions.